The religious and educational values in contemporary pinoy rock music: Perceptions of the senior high school students of Divine World College Legazpi - Reyes, Noel B. (Animo Repository, 2007)
Different kinds of music draw out different effects to the listeners’ physical, mental or emotional and spiritual aspects. Rock music is the youth music and its their way of addressing their social, spiritual problems and express their emotions. According to Frith (1981) and Weintein (1994), rock music is inseparable from the youth; and as long as youth exists rock music exists, too. This is why rock music is so appealing to the youth even if it produces aberrant behavior. Because of this, there is a need to determine the religious and educational values of rock music. It is in this light that the researcher pursued to conduct a study on the perceive religious and educational values by the senior high school students of Divine Word College of Legazpi in Contemporary Pinoy rock music. This study was designed to effectively determine the religious and educational values in contemporary Pinoy Rock compositions as perceived by the senior high school students of Divine Word College of Legazpi. Pinoy rock music can be used to inculcate in them a sense of responsibility, to be properly educated and guided in their choice of music and not to leave the freedom of listening to rock music all by themselves. It can also be used to strengthen Christian values learned in their daily life experiences and practices. This study used the classroom as the venue to prove that the students’ perception regarding the religious and educational values in contemporary Pinoy rock compositions are true and jibe with the Gospel values. The respondents of the study vii vii were 200 senior high school students of Divine Word College of Legazpi for the School Year 2006-2007. The age range was 15 to 16 years old. The following were the procedures and methods used: 1) A preliminary survey of the top 5 popular contemporary Pinoy rock music compositions and bands was conducted. 2) a preliminary survey of the religious and educational values perceived by the youth in contemporary Pinoy rock followed. 3 the checklist was formulated, administered, retrieved and organized. An evaluation of the measurability of the instruments used and statistical treatment was conducted also. 4) A lesson was conducted using the top contemporary Pinoy rock music composition “Liwanag sa Dilim” as a motivational teaching-learning tool 5.) An evaluative questionnaire was administered after conducting the lesson to come up with the religious and educational implications. The evaluative questionnaire was retrieved and then the responses were analyzed and organized. The checklist and the evaluative questionnaire belong to the primary data. The checklist was used to determine the most popular contemporary Pinoy rock composition and band, and the perceived religious and educational values. The evaluative questionnaire determined the implications in the religious and educational practices of the students. The data implied that religious and educational values can be learned from some contemporary Pinoy rock music. Empirical method of the study was included, aside from theories because the present study is new in its local field. Frequency count, percentage and rank were used to describe the data.